2017
DOI: 10.1111/bdi.12487
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine versus midazolam in bipolar depression with suicidal thoughts: A pilot midazolam‐controlled randomized clinical trial

Abstract: The study demonstrated feasibility. Suicidal thoughts were lower after ketamine than after midazolam at a trend level of significance, likely due to the small pilot sample. Memory improvement and BDNF are promising biomarkers. Replication is needed in an adequately powered full-scale trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 41 publications
5
98
1
4
Order By: Relevance
“…Somewhat surprisingly, plasma BDNF levels were not associated with responder class. Previous studies of bipolar, but not MDD, samples found that plasma BDNF levels were associated with SI response after ketamine (Grunebaum, 2017; Grunebaum et al, 2017), suggesting that the mixed diagnostic composition of this study may explain differences from previous work. Studies exploring the relationship between BDNF and antidepressant response to ketamine have also yielded mixed findings (Haile et al, 2014; Machado-Vieira et al, 2009).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Somewhat surprisingly, plasma BDNF levels were not associated with responder class. Previous studies of bipolar, but not MDD, samples found that plasma BDNF levels were associated with SI response after ketamine (Grunebaum, 2017; Grunebaum et al, 2017), suggesting that the mixed diagnostic composition of this study may explain differences from previous work. Studies exploring the relationship between BDNF and antidepressant response to ketamine have also yielded mixed findings (Haile et al, 2014; Machado-Vieira et al, 2009).…”
Section: Discussioncontrasting
confidence: 66%
“…Further study is needed to determine which of these approaches will prove more fruitful. Complete remission of SI has previously been used as an outcome measure in clinical trials and in a meta-analysis of ketamine’s efficacy (Grunebaum et al, 2017; Grunebaum et al, 2018; Wilkinson et al, 2017), as well as in a study examining the relationship between SI response to ketamine and changes in nocturnal wakefulness (Vande Voort et al, 2017). One strength of the present study is that this data-driven approach provides classifications that directly reflect the phenomena under study as they are, as opposed to what they should be.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, ketamine has a rapid and long-lasting antidepressant effect in both MDD and BD (Grunebaum et al, 2017;Vande et al, 2017;Kadriu et al, 2018). Our results in this study suggest that ketamine also has a significant improvement in POD, and this beneficial effect could be totally attenuated by TrkB antagonist ANA-12, suggesting that BDNF-TrkB signaling plays an important role in ketamine exerting antidepressant effects in POD.…”
Section: Discussionsupporting
confidence: 78%
“…At least 2 RCTs, 18,19 not included in the meta-analyses discussed, 13,15 have recently been published. Both RCTs recruited patients with clinically significant suicidal ideation, operationalized as a Scale for Suicidal Ideation (SSI) score of at least 4.…”
Section: Recent Randomized Controlled Trials Of Ketamine In Patients mentioning
confidence: 99%
“…In the first RCT, 18 16 patients with bipolar depression and clinically significant suicidal ideation were randomized to receive IV ketamine (0.5 mg/kg) or midazolam (0.02 mg/kg); ongoing psychotropics, barring benzodiazepines, were continued unchanged during the study. One day after treatment, SSI scores attenuated substantially and nearsignificantly more with ketamine than with midazolam.…”
Section: Recent Randomized Controlled Trials Of Ketamine In Patients mentioning
confidence: 99%